The Influence of Advertising on Wardah Cosmetic Purchasing Decisions (Case Study of Germasa GPIB Petra Women) - Anisti Anisti; Tuty Mutiah; Kristina Natalia (Jurnal Indonesia Sosial Teknologi, 2024)
Advertising plays an important role in influencing consumer perceptions and attitudes towards products, especially for well-known brands like Wardah. Advertising strategies help build a positive image and increase consumer interest. Research shows that consumers are more likely to buy products from well-known brands than lesser-known brands. Wardah, which is widely known by Germasa GPIB Petra women, allows consumers to recognize and create their image. Wardah's advantages include a halal guarantee from MUI and its availability in various online and offline stores. Quantitative research method This research examines the influence of advertising on consumer purchasing decisions based on syringe theory. The validity and reliability of the questionnaire are adequate (Cronbach's alpha 0.749). The analysis shows that the effect of advertising is very small (R² 0.030%). Although the T-test shows a significant impact (count 4.384 Table 2.0106), overall, the effect of advertising is not substantial (0.02958%). Internal and interpersonal factors are more dominant, so the syringe theory is not fully proven. Research shows that Wardah product advertisements have a significant influence on purchasing decisions (reliability 0.766 and 0.749). The hypothesis is accepted, but the R Square value of 0.030% shows a very small effect. GPIB Petra's female consumers rely more on personal experience and other factors than advertising, so advertising does not play a significant role in purchasing decisions.